(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2020)
Molecular hydrogen (H2) and ethanol are the main by-products of glycerol fermentation by Escherichia coli. In this study, the growth of E. coli BW25113 was investigated with the addition of small amounts (0.05 to 2 %) of ethanol alone and in a combination with glycerol The bacterial growth, the kinetic of the redox potential, and the H2 production in peptone medium, pH 7.5, were investigated upon various amounts of ethanol supplementation. In the presence of any amount of ethanol, but upon the absence of other sources of carbon, no H2 production was observed. Whereas ethanol (0.3 to 1 %) with a combination of glycerol stimulated both bacterial growth and H2 production, pH 7.5. A correlation was observed between the redox potential and stimulated by ethanol bacterial growth. The obtained results can be applied to regulate fermentation processes in biotechnology.